2023
DOI: 10.1038/s41467-023-43007-6
|View full text |Cite
|
Sign up to set email alerts
|

Reversed asymmetric warming of sub-diurnal temperature over land during recent decades

Ziqian Zhong,
Bin He,
Hans W. Chen
et al.

Abstract: In the latter half of the twentieth century, a significant climate phenomenon “diurnal asymmetric warming” emerged, wherein global land surface temperatures increased more rapidly during the night than during the day. However, recent episodes of global brightening and regional droughts and heatwaves have brought notable alterations to this asymmetric warming trend. Here, we re-evaluate sub-diurnal temperature patterns, revealing a substantial increase in the warming rates of daily maximum temperatures (Tmax), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 88 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…Due to the large coverage and diverse vegetation types in the study area, as well as significant variations in NPP for different vegetation types under different climatic and seasonal conditions, future research should focus on further subdividing vegetation types and exploring the changing trends of vegetation NPP in different seasons and over longer time scales in the SHRC. Additionally, in analyzing the relationship between NPP and climatic factors, here we only considered multiple temperature factors and precipitation and did not incorporate other factors such as the regional atmospheric circulation, solar radiation, evapotranspiration, atmospheric water vapor or cloud cover into the impact of climate change on vegetation NPP [ 25 , 27 , 50 ]. These omissions may introduce some uncertainty into the results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to the large coverage and diverse vegetation types in the study area, as well as significant variations in NPP for different vegetation types under different climatic and seasonal conditions, future research should focus on further subdividing vegetation types and exploring the changing trends of vegetation NPP in different seasons and over longer time scales in the SHRC. Additionally, in analyzing the relationship between NPP and climatic factors, here we only considered multiple temperature factors and precipitation and did not incorporate other factors such as the regional atmospheric circulation, solar radiation, evapotranspiration, atmospheric water vapor or cloud cover into the impact of climate change on vegetation NPP [ 25 , 27 , 50 ]. These omissions may introduce some uncertainty into the results.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in analyzing the relationship between NPP and climatic factors, here we only considered multiple temperature factors and precipitation and did not incorporate other factors such as the regional atmospheric circulation, solar radiation, evapotranspiration, atmospheric water vapor or cloud cover into the impact of climate change on vegetation NPP [25,27,50]. These omissions may introduce some uncertainty into the results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Cook and Vizy (2015) found that from 1979 to 2012, the Sahara Desert warmed 2-4 times more than all It can be thought that "diurnal asymmetric warming" also plays an important role in the change in the number of tropical nights in the Mediterranean Basin. Indeed, the land surface air temperature observations showed that evidently nights have been warming much faster than days, and daily minimum temperatures have increased about 40% faster than daily maximum temperatures due to changes in the cloud cover, solar radiation, aerosols, precipitation, planetary boundary layer depth, land use change and deforestation in the latter half of the twentieth century (Davy et al, 2017;Doan et al, 2022;Zhong et al, 2023;Zhou, 2021). The asymmetry is most substantial at the surface, gradually decreases with height, and disappears above approximately 1 km from the ground.…”
Section: Conclusion and Discussionmentioning
confidence: 99%